2004
DOI: 10.20965/jaciii.2004.p0168
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Motion Characteristics Corresponding to Sensitivity Information Using Dance Movement

Abstract: This study is intended to quantitatively clarify the relationship between the motion characteristics behind the human motion in complicated motions like dancing and the subjective impressions of the observer. It examines the impression structures related to the motion of a determined body part of dancing and considers the motion characteristics giving a specific impression. To compare and consider the impression structures related to the motion of a body part, the authors made a principal component analysis, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Most recent automatic recognition research makes use of either body posture or movement as the source of affective information whereas many early developments have focused on recognizing emotions from expressive dance (e.g. Camurri et al, 2003;Camurri et al, 2004;Park et al, 2004;Kamisato et al, 2004). Camurri and colleagues (Camurri et al, 2003;Camurri et al, 2004) extracted dynamic motion cues from dancers' body movements to differentiate between basic emotions.…”
Section: Automatic Emotion Recognition From Bodily Expressionsmentioning
confidence: 99%
“…Most recent automatic recognition research makes use of either body posture or movement as the source of affective information whereas many early developments have focused on recognizing emotions from expressive dance (e.g. Camurri et al, 2003;Camurri et al, 2004;Park et al, 2004;Kamisato et al, 2004). Camurri and colleagues (Camurri et al, 2003;Camurri et al, 2004) extracted dynamic motion cues from dancers' body movements to differentiate between basic emotions.…”
Section: Automatic Emotion Recognition From Bodily Expressionsmentioning
confidence: 99%
“…In the affective computing field, models for the automatic recognition of discrete emotion categories from static body postures have been proposed [2][5] [15]. Other studies have shown that body motions extracted from dance sequences [3] [24] [14] can convey emotion in terms of discrete categories effectively. To our knowledge, what are missing still are models for the automatic recognition of affective dimensions from posture as there are for motion [4].…”
Section: Introductionmentioning
confidence: 99%
“…Studies following this idea differ methodological by either exposing viewers to real actors playing [23], video scene of actors playing [2], computer animations of virtual humans [26], [27], point-light animations that conceptualize human body movements [28], [29], [30], [31], [22], or drawn figures [32]. The results of these and similar studies show that affective states can be identified by observing static postures [33], [26], [34], [35] or moving behavior [36], [37], [23], [2].…”
Section: Introductionmentioning
confidence: 99%